People's Republic of China-Hong Kong Special Administrative Region : Staff Report for the 1999 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2000)
Hong Kong Special Administrative Region (SAR) underwent a painful period of recession and adjustment during the Asian crisis. The adjustment in prices under the linked exchange rate system is well under way. Fiscal policy should continue to provide support for the recovery. Unemployment has stabilized but remains high. The banking system is resilient to external shocks. Technological changes in key service industries and the evolving relationship with the Mainland will lead to major structural changes in the Hong Kong SAR economy.